Ionic liquid decorated mesoporous silica nanoparticles: a new high-performance hybrid electrolyte for lithium batteries. Issue 23 (1st March 2016) - Li, Yang; Wong, Ka-Wai; Ng, Ka-Ming
Abstract : We report a novel hybrid electrolyte based on mesoporous silica nanoparticles decorated with an ionic liquid, which exhibits a superior lithium ion transference number of >0.8, and an excellent electrochemical window of >5 V with attractive ionic conductivity. Abstract : We report a novel hybrid electrolyte based on mesoporous silica nanoparticles decorated with an ionic liquid, which exhibits a superior lithium ion transference number of >0.8, and an excellent electrochemical window of >5 V with attractive ionic conductivity. The insights obtained pave a new way for the preparation of high-performance electrolytes with mesoporous structures.